Optimal fermentation parameters for processing high quality african locust bean condiments - AGBOBATINKPO, BIDOSSESSI PÉLAGIE (My University, 2019)
Fermented African locust bean (ALB) condiments are widely used to enhance the aroma and the taste of various dishes in West Africa. They are a good source of proteins. Sonru is one of the ALB condiments processed in Benin using a traditional starter called yanyanku. The variability in sonru processing unit operations (e.g. fermentation) presumably affects the quality (microbiological, biophysical and sensorial) of the ﬁnal product. This study aimed at optimizing the fermentation step of sonru based on response surface methodology including three-factors [i.e. proportion of yanyanku, fermentation duration and thickness/depth of the layer of ALB (TALB)] and three level factorial Box Behnken design with four central point replicates. The pH, softness of fermented cotyledons, Bacillus spp. and aerobic mesophilic bacteria count of sonru were evaluated. In addition, consumer acceptability was assessed by 7-hedonic box scale and Just About Right analysis. The pH had an upward trend with the increasing of all factors, and particularly Bacillus spp. count had similar trend with the fermentation duration and TALB whereas maximal penetration force (referred as the soft- ness) had a downward trend with the fermentation duration. The optimal fermented ALB condiment resulted from processing conditions set at 1% of yanyanku, 24 h of fermentation and 8.5 cm for TALB. The optimized sonru appeared to be ideal in color, softness and taste. These ﬁndings can be used to improve fermented ALB condiments processing and better control the product quality in African countries. Further studies are needed to improve the odor of sonru.
Keywords: African locust bean; sonru; process; optimization consumer acceptability; penalty analysis